EFFECT OF COMPUTERISATION OF LIBRARY ON STUDENT’S ACADEMY PERFORMANCE - MD. IRSHAD ALAM (International Journal of Multidisciplinary Research and Studies, 2021)
The library is an organisation that is expanding at a rapid rate; consequently, the traditional practises for its upkeep are no longer dynamic and efficient for expeditions, retrieval and dissemination of information, and improved service for the students. Instead, the implementation of contemporary practises has become an absolute necessity. A library that has been adequately digitised will be able to provide its patrons with services that are both rapid and timely. In an automated or electronic library, often known as a digital library, tasks such as accessing, sharing, and storing resources are carried out with the assistance of computers. The concept of "digital" refers to having a grasp of how electronic circuits are designed and developed. It encompasses methods such as word processing, micrographic, reprographic, and video-based information systems, as well as methods of message delivery such as faxing, voice mail, electronic mail, and the internet (Encyclopedia, 2013).